Activator protein 1 is a key terminal mediator of inflammation‐induced preterm labor in mice. Issue 5 (4th February 2014) - MacIntyre, David A.; Lee, Yun S.; Migale, Roberta; Herbert, Bronwen R.; Waddington, Simon N.; Peebles, Donald; Hagberg, Henrik; Johnson, Mark R.; Bennett, Phillip R.
ABSTRACT: Activation of uterine inflammatory pathways leads to preterm labor (PTL), associated with high rates of neonatal mortality and morbidity. The transcription factors nuclear factor κB (NFκB) and activator protein 1 (AP‐1) regulate key proinflammatory and procontractile genes involved in normal labor and PTL. Here we show that (NFκB) activation normally occurs in the mouse myometrium at gestation day E18, prior to labor, whereas AP‐1 and JNK activation occurs at labor onset. Where labor was induced using the progesterone receptor antagonist RU486, NFkB and AP‐1/JNK activation both occurred at the time of labor (20 h compared to 60 h in DMSO‐treated controls). Using an LPS ( Escherichia coli: serotype O111)‐induced PTL model that selectively activates AP‐1 but not NFkB, we show that myometrial AP‐1 activation drives production of cytokines ( Il‐6, Il‐8, and Il‐1 β), metalloproteinases ( Mmp3 and Mmp10 ), and procontractile proteins ( Cox‐2 and Cx43 ) resulting in PTL after 7 h. Protein levels of CX43 and IL‐1β, and IL‐1β cleavage, were increased following LPS‐induced activation of AP‐1. Inhibition of JNK by SP600125 (30 mg/kg) delayed PTL by 6 h (7.5 vs . 13.5 h P <0.05). Our data reveal that (NFκB) activation is not a functional requirement for infection/inflammation‐induced preterm labor and that AP‐1 activation is sufficient to drive inflammatory pathways that cause PTL.—MacIntyre, D. A., Lee, Y. S., Migale, R., Herbert, B. R., Waddington, S. N., Peebles, D., Hagberg, H., Johnson, M. R., Bennett, P. R. Activator protein 1 is a key terminal mediator of inflammation‐induced preterm labor in mice. FASEB J . 28, 2358–2368 (2014). www.fasebj.org